2001
DOI: 10.1177/000331970105200507
|View full text |Cite
|
Sign up to set email alerts
|

Paget-Schroetter Syndrome in Sports Activities

Abstract: The authors report 7 patients with thromboses in the upper extremity resembling Paget-Schroetter syndrome. According to their case histories, all patients had a temporal and causal relationship between partially unusual sports activities and the genesis of the thrombosis. The cause of this condition is a strain on the subclavian and axillary veins by retroversion or hyperabduction of the arm. This can entail microtraumatizations of the venous intima, consequently leading to a consecutive local activation of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 22 publications
2
63
1
3
Order By: Relevance
“…The mechanism of idiopathic thrombosis may be as follows: the costoclavicular space becomes narrow when the shoulder moves posteroinferiorly or when the arm is excessively abducted or rotated externally, so that the subclavian vein is compressed between the first rib and the clavicle. Actions that repeatedly and excessively apply such compression to the subclavian vein can lead to the onset of phlebitis and venous thrombosis (8,9). As a scaffold constructor, this patient carried steel scaffold frames on his right shoulder every day for over 20 years and such occupational compression of the subclavian vein probably led to the onset of phlebitis, venous obstruction, and thrombosis that resulted in chronic pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanism of idiopathic thrombosis may be as follows: the costoclavicular space becomes narrow when the shoulder moves posteroinferiorly or when the arm is excessively abducted or rotated externally, so that the subclavian vein is compressed between the first rib and the clavicle. Actions that repeatedly and excessively apply such compression to the subclavian vein can lead to the onset of phlebitis and venous thrombosis (8,9). As a scaffold constructor, this patient carried steel scaffold frames on his right shoulder every day for over 20 years and such occupational compression of the subclavian vein probably led to the onset of phlebitis, venous obstruction, and thrombosis that resulted in chronic pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, it is rare for idiopathic upper limb venous thrombosis to occur without any underlying disease, and this condition is known as Paget-Schroetter syndrome (7) or effortrelated axillo-subclavian vein thrombosis (8). Idiopathic subclavian thrombosis is thought to be caused by excessive abduction and excessive external rotation of the upper extremities, such as occurs during throwing sports and heavy manual labor (9). The subclavian vein is most commonly affected by idiopathic or primary upper limb venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…shelving jobs, porterage, hod-carrying, hammering, swimming, wrestling, volleyball or handball, tennis or squash, baseball, and bodybuilding (2,4,8,10). In an uncontrolled retrospective analysis of a series of 27 patients with primary subclavian venous thrombosis, Zell et al (8) reported that 24 had exerted unusual physical strain for several days or weeks and apparently fulfilled the criteria for occupational disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly classified as primary or secondary (1). Primary subclavian thrombosis-also known as "effort thrombosis" or PagetSchroetter syndrome-occurs in the absence of recognized risk factors or diseases (central venous catheter, malignancies, hypercoagulability, effects of surgery) and is often associated with repetitive or strenuous exercise (1,2). It is often associated with compressioninduced neurovascular disorders between the neck and shoulder commonly known as "thoracic outlet syndrome" (3,4).…”
mentioning
confidence: 99%
“…Ağır efor damar intimasında mikrotravmalara yol açarak endotel hasarına neden olur ve koagulasyon döngüsünü başlatır. Tekrarlayan ve şiddetli hareketler sonucunda subklavian vende trombüs formasyonu başlayarak ven oklüzyonu görülür (13,14).…”
Section: Patogenezunclassified